(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The New Curricula are aimed at making the teaching of literary modules even more interesting and interactive, mostly through the integration of ICT. This proposal deals with the inclusion of ICT, and more specifically, the Nearpod digital learning application, as well as the use of the cooperative group method, learning through exploratory processes, and the development of the students critical ability on the subject of Latin. The proposed teaching scenario refers to assigning group projects, based on the students ’learning profiles’, on the topic of the Death Penalty. In more particular, for the implementation of the scenario, the following techniques are utilized: cooperative group teaching, the question-answer and discussion technique, agency, use of digital media, use of digital resources, and exploratory learning.